Role Playing Learning Method as A Solution to Improve The Learning Outcomes of Civic Education Elementary School Students of Election and Election Materials - Rikmasari, Rima; Summirat, Fanny; Pratiwi, Firda Ajeng (Edukasi, 2021)
The implementation of the Role Playing Method is a learning method in which students can be involved in planned learning activities designed based on experience by playing roles to improve learning outcomes of PKN (Civic Education) elementary school students on election and regional election material. The implementation of the Role Playing method is very effective in improving student learning outcomes. The impact of using the Role Playing method is an increase in student understanding, students are trained to take initiative and be creative and the ability to solve problems according to the content of the story discussion.